2006
DOI: 10.1016/j.virol.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation at a lysine residue adjacent to the CtBP binding motif within adenovirus 12 E1A causes structural disruption and limited reduction of CtBP binding

Abstract: C-terminal binding protein (CtBP) has been shown to bind to a highly conserved five-amino-acid motif (PXDLS) located very close to the C-terminus of adenovirus early region 1A proteins. It has also been demonstrated that amino acids C-terminal and N-terminal to this original proposed binding site contribute to the interaction. However, conflicting evidence has been presented to show that acetylation of an adjacent lysine residue in Ad5E1A may or may not influence binding. It has now been demonstrated here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Therefore, the exact position of the acetylated lysine residue relevant to the transcriptional regulation is not important, but the important lysine residue is probably localized within a few amino acids just after the CtBP-binding motif. On the other hand, it has been reported that the acetylation at Lys 239 adjacent to the CtBPbinding motif in E1A causes a limited reduction in its CtBP binding ability as revealed by in vitro binding assays using synthetic peptides (29). In EVI1, CtBP2 was retained in the protein complex with EVI1 and P/CAF on the DNA at the GATA2 promoter region; however, HDAC1 was not included in this protein complex.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the exact position of the acetylated lysine residue relevant to the transcriptional regulation is not important, but the important lysine residue is probably localized within a few amino acids just after the CtBP-binding motif. On the other hand, it has been reported that the acetylation at Lys 239 adjacent to the CtBPbinding motif in E1A causes a limited reduction in its CtBP binding ability as revealed by in vitro binding assays using synthetic peptides (29). In EVI1, CtBP2 was retained in the protein complex with EVI1 and P/CAF on the DNA at the GATA2 promoter region; however, HDAC1 was not included in this protein complex.…”
Section: Discussionmentioning
confidence: 97%
“…However, the cytoplasmic localization of K239A-E1A may complicate the interpretation (Madison et al, 2002). A recent study using K239-acetylated E1A peptides suggested that Lys239 acetylation may modestly reduce the affinity for CtBP in vitro by inducing structural changes (Molloy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that CtBP activity can be regulated by acetylation of CtIPs such as E1A and RIP140. In both cases, acetylation of lysine residues flanking the PXDLS-binding motif located in these proteins results in decreased CtBP association and reduced transcriptional repression (58)(59)(60). Thus, CtBP activity can be regulated indirectly by enhancing or inhibiting its ability to bind CtBP-interacting partners.…”
Section: Post-translational Modificationsmentioning
confidence: 99%